Experimental analysis on the performance and emissions of diesel/butanol/biodiesel blended fuels in a flame tube boiler. (5th February 2018) - Kilic, Gokhan; Sungur, Bilal; Topaloglu, Bahattin; Ozcan, Hakan
Highlights: Butanol/biodiesel blended fuels decreased the size of the peak temperature zones. CO emissions decreased significantly from 281 ppm to 4.5 ppm by using D70B30. NOx emissions did not change considerably, remained by about 46–48 ppm. Efficiencies increased from 90.5% to 90.8% by using D70B30 fuel. Abstract: This paper presents an experimental study of combustion of diesel/butanol/biodiesel blended fuels and their effect on boiler performance and emissions in a reversal flame tube boiler. Pure diesel, blends of diesel/butanol, and blends of diesel/butanol/biodiesel were used in the experiments. Before the combustion experiments, the miscibility of different fuel types was examined. To investigate the characteristics of combustion by using different fuel blends, the temperature distributions in the combustion chamber and smoke tube were determined. Exhaust gas temperature and exhaust gas emissions were measured in the boiler exit. The results showed that by using diesel/butanol blends the size of the peak temperature zones in the combustion chamber decreased gradually from D100 to D70B30. As a consequence of better combustion conditions in the combustion chamber, CO emissions decreased gradually from 281 ppm to very low values of 4.5 ppm, exhaust temperature decreased nearly 13 °C and efficiency increased nearly 0.3%, from D100 to D70B30. In triple mixtures, as the amount of biodiesel in the mixture increases, the maximum temperature in the boiler also increased compared to D70B30 and the amount of CO also increased. Also, NOx emissions did not change significantly in all experiments and remained by about 46–48 ppm.